2012
DOI: 10.1016/j.molcel.2012.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometry of the CD95 Death-Inducing Signaling Complex: Experimental and Modeling Evidence for a Death Effector Domain Chain Model

Abstract: The CD95 (Fas/APO-1) death-inducing signaling complex (DISC) is essential for the initiation of CD95-mediated apoptotic and nonapoptotic responses. The CD95 DISC comprises CD95, FADD, procaspase-8, procaspase-10, and c-FLIP proteins. Procaspase-8 and procaspase-10 are activated at the DISC, leading to the formation of active caspases and apoptosis initiation. In this study we analyzed the stoichiometry of the CD95 DISC. Using quantitative western blots, mass spectrometry, and mathematical modeling, we reveal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
181
2
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 175 publications
(197 citation statements)
references
References 63 publications
(82 reference statements)
12
181
2
2
Order By: Relevance
“…The relative abundance of the different cleavage products for procaspase-8 in each slice was quantified by AQUA peptide-based mass spectrometry as described before (Supplementary Figure S2). 29,31 Similar to the western blot quantifications, the relative amounts of the procaspase-8 prodomain p26/p24 at the DISC increased over time (Figure 1e). This quantification further confirmed that the prodomain of procaspase-8a/b p26/p24 is a major part of the DED chains at the CD95 DISC, while the cleavage product p43/p41 is present in lower amounts.…”
Section: Resultssupporting
confidence: 65%
See 4 more Smart Citations
“…The relative abundance of the different cleavage products for procaspase-8 in each slice was quantified by AQUA peptide-based mass spectrometry as described before (Supplementary Figure S2). 29,31 Similar to the western blot quantifications, the relative amounts of the procaspase-8 prodomain p26/p24 at the DISC increased over time (Figure 1e). This quantification further confirmed that the prodomain of procaspase-8a/b p26/p24 is a major part of the DED chains at the CD95 DISC, while the cleavage product p43/p41 is present in lower amounts.…”
Section: Resultssupporting
confidence: 65%
“…27,28 Recently, we studied the stoichiometry of the CD95 DISC by AQUA peptide-based mass spectrometry. 29 In combination with western blot analysis supported by mathematical modeling, we revealed an unexpected stoichiometry in which procaspase-8 is more abundant at the DISC compared with FADD. 29 Similar results were obtained for the TRAIL DISC.…”
mentioning
confidence: 70%
See 3 more Smart Citations